Corrosion of reinforced concrete bridges - Ismail, Mohamad (1993)
Deterioration of steel reinforcement in bridges and marine structures subjected to aggressive environment pose major problem to the concrete construction industry in many countries. This paper presents two case studies with respect to corrosion conducted on reinforced concrete bridges in Malaysia. The results of NDT show that the steel reinforcement in bridges are experiencing corrosion whilst the chemical tests undertaken seems to confirm that chloride attack and carbonation are the major factors contributing to the corrosion process.